The effects of 24-week prebiotic intervention on markers of immunity and upper respiratory and gastrointestinal symptoms in elite rugby union players: a pilot randomised controlled trial - Parker, C. J.; Johnson, M. A.; Hunter, K. A.; Sharpe, G. R.; Williams, N. C. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Elite athletes are exposed to physiological and psychological stressors that may impair immunity and increase the risk of upper respiratory (URS) and gastrointestinal symptoms (GIS). Gut microbes have a substantial influence on systemic immune function (Roberfoid et al., 2010). Dietary prebiotic galactooligosaccharides are effective at altering the gut microbiome and have been shown to reduce URS in academically stressed students (Hughes et al., 2011). Whether prebiotics could also reduce URS and GIS in elite athletes is unclear. Therefore, the aim of this study was to investigate the effect of a 24-week prebiotic intervention on markers of immunity and URS and GIS in elite rugby union players during a regular playing season.